2012
DOI: 10.1136/bjsports-2011-090439
|View full text |Cite
|
Sign up to set email alerts
|

Sports medicine, confidentiality and the press

Abstract: English newspapers are replete with athletes' medical details, with football dominant. A significant risk to clinicians' professional status exists if they collude to release the un-consented confidential medical information to those with no direct involvement in athletes' medical care. Athletes' education as to their rights as patients and to sports medicine professionals as to their obligations are urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 11 publications
(8 reference statements)
3
16
0
Order By: Relevance
“…3,510,12,14,20 When working with sports teams, clinicians may experience dual loyalties toward in dividual players and the team, which may be a source of tension in regard to obli gations and expectations. 7,8,15,20 Concerns have also been raised about disclosure by clinicians of athletes' confidential infor mation to the media. 15 Swisher et al 19 identified ethical issues experienced by an expert group composed of certified athletic trainers from the Unit ed States.…”
Section: Participantsmentioning
confidence: 97%
See 1 more Smart Citation
“…3,510,12,14,20 When working with sports teams, clinicians may experience dual loyalties toward in dividual players and the team, which may be a source of tension in regard to obli gations and expectations. 7,8,15,20 Concerns have also been raised about disclosure by clinicians of athletes' confidential infor mation to the media. 15 Swisher et al 19 identified ethical issues experienced by an expert group composed of certified athletic trainers from the Unit ed States.…”
Section: Participantsmentioning
confidence: 97%
“…7,8,15,20 Concerns have also been raised about disclosure by clinicians of athletes' confidential infor mation to the media. 15 Swisher et al 19 identified ethical issues experienced by an expert group composed of certified athletic trainers from the Unit ed States. Participants then rated 154 ethi cal issues according to their importance and frequency.…”
Section: Participantsmentioning
confidence: 97%
“…Also, the Russian doping raised a doubt on the candour of the Olympics Games. On the other hand, the American sports (e.g NFL and NHL) are creating protocols to improve protection to athletes disclosing concussion information (Kerr et al, 2014;Ribbans et al, 2013).…”
Section: • Authenticitymentioning
confidence: 99%
“…the internet) has heightened this issue. Consequently medical information appears throughout the media and while there may be multiple sources for that information, the pressures on clinical staff to release confidential patient data are considerable [26]. In an age where professional reputations and commercial value are fostered via social media, the incentives to act unethically are increased [27].…”
Section: Contextual Factors Influencing Confidentiality In Sports Medmentioning
confidence: 99%